Effectiveness of Nanohydroxyapatite on Demineralization of Enamel and Cementum Surrounding Margin of Yttria-Stabilized Zirconia Polycrystalline Ceramic Restoration - Niwut Juntavee; Apa Juntavee; Preeyarat Plongniras (The Scientific World Journal)
Introduction. Prosthetic dentistry has shifted toward prevention of caries occurrence surrounding restorative margin through the anti-demineralization process. This study examines the ability of nanohydroxyapatite (NHA) gel and Clinpro (CP) on enhancing resistance to demineralization of enamel and cementum at margin of restoration. Materials and Methods. Thirty extracted mandibular third molars were segregated at 1 mm above and below cementoenamel junction (CEJ) to separate CEJ portions and substituted with zirconia disks by bonding to crown and root portions with resin adhesive. The enamel and cementum area of 4 × 4 mm2 neighboring zirconia was applied with either NHA or CP, while one group was left no treatment (NT) before demineralized with carbopal. Vickers hardness (VHN) of enamel and cementum was evaluated before material application (BM), after material application (AM), and after demineralization (AD). Analysis of variance (ANOVA) and post hoc multiple comparisons were used to justify for the significant difference (α = 0.05). Scanning electron microscopy (SEM) and X-ray diffraction (XRD) were determined for surface evaluations. Results. The mean ± SD of VHN for BM, AM, and AD for enamel and cementum was 393.24 ± 26.27, 392.89 ± 17.22, 155.00 ± 5.68 and 69.89 ± 4.59, 66.28 ± 3.61, 18.13 ± 0.54 for NT groups, respectively, 390.10 ± 17.69, 406.77 ± 12.86, 181.55 ± 7.99 and 56.01 ± 9.26, 62.71 ± 6.15, 19.09 ± 1.16 for NHA groups, respectively, and 387.90 ± 18.07, 405.91 ± 9.83, 188.95 ± 7.43 and 54.68 ± 7.30, 61.81 ± 4.30, 19.22 ± 1.25 for CP groups, respectively. ANOVA indicated a significant increase in anti-demineralization of enamel and cementum upon application of NHA or CP (p<0.05). Multiple comparisons indicated the capability in inducing surface strengthening to resist demineralization for enamel and cementum of NHA which was comparable to CP (p>0.05) as evidenced by SEM and XRD data indicating NHA and CP deposition and crystallinity accumulation. Conclusion. NHA and CP were capable of enhancing anti-demineralization for enamel and cementum. The capability in resisting the demineralization process of NHA was comparable with CP. NHA was highly recommended for anti-demineralization for enamel and cementum surrounding restorative margin.